The Fall of PPP Governments in the 1990s: Political Rivalries and Corruption Allegations - Ali, Mahmood; Khalid, Muhammad Munib; Naseer, Husnain (Annals of Human and Social Sciences, 2025)
The PPP experienced multiple premature government terminates during the 1990s because political battles escalated with constant corruption accusations. This research investigates the essential political aspects together with institutional structures and governance components which caused the PPP governments to fall in 1990 and 1996. The research relies on qualitative methodology to study the political struggles and institutional observations as well as corruption cases through the examination of historical documentation and parliamentary proceedings and court decisions and media reports. The research demonstrates how corruption scandals significantly damaged PPP government credibility yet such allegations served multiple political groups such as opposition forces along with military suits and judicial bodies who used them to weaken democratic institutions. Executive-legislative tension alongside presidential discretionary powers created political instability in Pakistan’s system of governance according to the study. This research brings essential understanding about Pakistani democratic consolidation challenges while proposing institutional reforms which aim to enhance governance and accountability together with political stability.